Socio-Economic Impact Assessment of Small Dams Based on T-Paired Sample Test Using SPSS Software - Bhatti, Nabi Bux; Siyal, Altaf Ali; Qureshi, Abdul Latif; Bhatti, Imtiaz Ali (Salehan Institute of Higher Education, 2019)
A dam is a barrier/structure that impounds water and retains it for later use. Thus, it plays an important role and offers a reserve stock of water for rural communities in remote areas. The present study was conducted to assess the socio-economic impact of small dams on local communities. The impact was analyzed based on descriptive statistics and t- paired sample tests using SPSS software to study and analyze the Nagarparkar area, Sindh, Pakistan. Primary and secondary data were used for collecting the data. The data was collected randomly from 250 people through interviews and group discussions Also, 104 sets of data were obtained through a questionnaire survey. The overall results summary of the parameters revealed that a significantly positive variation occurred in the study area after construction of the dam. The number of the packa houses and water depth were increased. The distance to collect water and water-fetching time were decreased 6% and 5.61 % respectively. The overall average area cultivated with crops was increased by 26.55%. The average yield of almost every crop in both Rabi and Kharif seasons were increased by 55% in the areas surrounding the dams. The overall number of livestock was increased by 18.08%, while the number of horses decreased by 1.5% after construction of the dam. The income, expenditure, and savings have increased significantly to 36.16%, 17.68%, and 32.15%, respectively, while the migration rate has decreased19.09% since construction of the dam. The choice of crops has also changed from inferior crops to superior and market-oriented crops. The water table and quality have improved, and wells have been recharged.